Potential of PINK1 and PARKIN Proteins as Biomarkers for Active Multiple Sclerosis: A Japanese Cohort Study - Cossu, Davide; Yokoyama, Kazumasa; Sechi, Leonardo Antonio; Hattori, Nobutaka (Frontiers in Immunology, 2021)
Background: mitochondrial dysfunction has been suggested to play an important role in all stages of multiple sclerosis (MS) Objective: to determine the expression of two mitophagy-related proteins, PTEN-induced kinase 1 (PINK1) and PARKIN, in a cohort of Japanese patients with different neuroinflammatory disorders. Methods: protein concentrations were measured using commercial ELISA in paired cerebrospinal fluid (CSF) and serum samples from patients with multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), and myelin oligodendrocyte glycoprotein antibody disorders (MOGAD), and from age- and sex-matched controls. Results: CSF and serum concentrations of PINK1 were higher in patients with MS than in patients with NMOSD (p = 0.004 and p < 0.001, respectively), MOGAD (p = 0.008 and p = 0.011, respectively), and controls (p = 0.021 and p = 0.002, respectively). CSF and concentrations of PARKIN were elevated in patients with MS in comparison with those in controls (p = 0.016 and p = 0.05, respectively). Conclusions: our study highlighted the importance of mitophagy in MS and suggested the potential application of PINK1 and PARKIN as biomarkers to predict disease activity.